2009
DOI: 10.1021/ic900397r
|View full text |Cite
|
Sign up to set email alerts
|

Making a Robust Carbon−Cobalt(III) Bond

Abstract: The coordination ion with a well-characterized carbon-cobalt(III) bond, the (1,4,7-triazacyclononane)(1,6-diamino-3-thia-4-hexanido)cobalt(III) dication, [Co(tacn)(C-aeaps)](2+) (aeaps, for aminoethylaminopropylsulfide), has been reacted with iodomethane, and the S-methyl thionium derivative has been isolated. The crystal structure of the resulting [Co(tacn)(C-aeaps-SCH(3))]Br(3) x 3 H(2)O at 122 K has been determined by X-ray diffraction techniques to verify the structure. The crystal structure determination … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…Here we have to limit ourselves to offering a first impression of the kind of generality that can be expected, by including also a set of 10 TM complexes different from those analyzed above; see Scheme 2 and Table 2. The complexes involve transition metals of all three rows and count well-known alkene metathesis (19)(20), polymerization (21)(22)(23), oligomerization (24), hydroformylation (25,26), and hydrogenation (27), catalyst precursors. The derivative of Vaska's complex, with two oxidatively added hydride ligands (28), completes the set and underlines the focus on catalytic organometallic chemistry in the selection of representative complexes.…”
Section: Extension To Other Transition-metal Complexesmentioning
confidence: 99%
See 1 more Smart Citation
“…Here we have to limit ourselves to offering a first impression of the kind of generality that can be expected, by including also a set of 10 TM complexes different from those analyzed above; see Scheme 2 and Table 2. The complexes involve transition metals of all three rows and count well-known alkene metathesis (19)(20), polymerization (21)(22)(23), oligomerization (24), hydroformylation (25,26), and hydrogenation (27), catalyst precursors. The derivative of Vaska's complex, with two oxidatively added hydride ligands (28), completes the set and underlines the focus on catalytic organometallic chemistry in the selection of representative complexes.…”
Section: Extension To Other Transition-metal Complexesmentioning
confidence: 99%
“…For most TM complexes of practical use, structures from X-ray diffraction analyses remain the only standard against which to validate, and a number of such studies have been reported. [23][24][25][26][27][28][29] The overall impression from these studies is, as was noted above for validation studies against gas-phase geometries, that the functionals of choice depend heavily on the particular chemical system under study.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of two chloride ions outside of the coordination sphere satisfied the charge of the central metal ion. The average Co–N distance (1.982 Å) was found to be within the range of analogous reported complexes …”
Section: Resultsmentioning
confidence: 99%
“…Tacn has been used as a ligand system to produce a stable cobalt(III)-carbon bonded compound. 10 The six coordinate compound starts with an N 5 S coordination sphere followed by deprotonation of an aminoalkylsulfide ligand and a switch from S to C bonding which can then be locked in place by methylation of the sulfur. The data from the X-ray structural determination and DFT calculations were used to rationalise the bonding.…”
Section: Aza Macrocyclesmentioning
confidence: 99%